Teaching Speaking in Inclusive Schools - Zharylkasyn Gulsezim Muratkyzy; Jangeldinova Saltanat Bolatovna (Reviews of Modern Science, 2026)
Inclusive education has become one of the most important directions in modern educational systems. It aims to provide equal learning opportunities for all students, including learners with disabilities and special educational needs. In language education, teaching speaking skills in inclusive classrooms is especially significant because communication helps students participate actively in social and academic life. However, teachers often face challenges when teaching speaking in mixed-ability classrooms. This article discusses the importance of teaching speaking in inclusive schools, the difficulties teachers encounter, and effective strategies for improving students’ speaking abilities. The study also highlights the role of teachers, classroom environment, technology, and cooperative learning in developing speaking competence among all learners. Inclusive speaking activities help students build confidence, improve social interaction, and develop communicative competence in a supportive environment.